Association of statin use and clinical outcomes in heart failure patients: A systematic review and meta-analysis - Bielecka-Dabrowa, Agata (2019)
Background The role of statins in patients with heart failure (HF) of different levels of left ventricular ejection fraction (LVEF) remains unclear especially in the light of the absence of prospective data from randomized controlled trials (RCTs) in non-ischemic HF, and taking into account potential statins’ prosarcopenic effects. We assessed the association of statin use with clinical outcomes in patients with HF. Methods We searched PubMed, EMBASE, Scopus, Google Scholar and Cochrane Central until August 2018 for RCTs and prospective cohorts comparing clinical outcomes with statin vs non-statin use in patients with HF at different LVEF levels. We followed the guidelines of the 2009 PRISMA statement for reporting and applied independent extraction by multiple observers. Meta-analyses of hazard ratios (HRs) of effects of statins on clinical outcomes used generic inverse variance method and random model effects. Clinical outcomes were all-cause mortality, cardiovascular (CV) mortality and CV hospitalization. Results Finally we included 17 studies (n = 88,100; 2 RCTs and 15 cohorts) comparing statin vs non-statin users (mean follow-up 36 months). Compared with non-statin use, statin use was associated with lower risk of all-cause mortality (HR 0.77, 95% confidence interval [CI], 0.72–0.83, P < 0.0001, I2 = 63%), CV mortality (HR 0.82, 95% CI: 0.76–0.88, P < 0.0001, I2 = 63%), and CV hospitalization (HR 0.78, 95% CI: 0.69–0.89, P = 0.0003, I2 = 36%). All-cause mortality was reduced on statin therapy in HF with both EF < 40% and ≥ 40% (HR: 0.77, 95% Cl: 0.68–0.86, P < 0.00001, and HR 0.75, 95% CI: 0.69–0.82, P < 0.00001, respectively). Similarly, CV mortality (HR 0.86, 95% CI: 0.79–0.93, P = 0.0003, and HR 0.83, 95% CI: 0.77–0.90, P < 0.00001, respectively), and CV hospitalizations (HR 0.80 95% CI: 0.64–0.99, P = 0.04 and HR 0.76 95% CI: 0.61–0.93, P = 0.009, respectively) were reduced in these EF subgroups. Significant effects on all clinical outcomes were also found in cohort studies’ analyses; the effect was also larger and significant for lipophilic than hydrophilic statins. Conclusions In conclusion, statins may have a beneficial effect on CV outcomes irrespective of HF etiology and LVEF level. Lipophilic statins seem to be much more favorable for patients with heart failure.